(untitled) (International Journal of Engineering and Computer Science, 2014)
The Side real Day many organization addresses problems nonstop growth of user huge increasing consumption of high performance of data storage. The dynamic data is very expensive and important to the organization and handle to that data organization needs very qualified or responsible people. Cloud service provider(CSP) offers the Lease facility for cloud model Storage -as- a-service which enables user to store his data in secured form on remote server. The Storage as service (SaaS) helps to reduce cost and maintenance level of organization end. Organization outsources their data on remote server to minimize the burden of huge local data and store on remote server. Data owner, Creates the specific level of security. If, any misbehavior by owner than it will pay for that to the CSP. Now a days, the Growth of cloud computing technology ratio also increasing in the world because of their security concern. Cloud computing many security issues related to securing data and examination of utilization of cloud by user. In this paper, We use the reliable Infrastructure of Cloud storage that provide the data owners all facilities offered by cloud and establishes the mutual trust between user and cloud. The following four remarkable features offered by our proposed system: • It permitted owner to store dynamic and sensitive data and performance the full block level dynamic operation (i.e modification, insertion, deletion and append). • It permitted to registered user rights to access the owners files and latest version of updated dynamic data. • It permitted to owner having control the access of outsource data (i.e. grant & revoke control access ) . • It establishes trust between the owner and cloud.